Implementation of Problem-Based Learning Model with Three-Dimensional Media and Interactive Games to Improve 3 Domains of Student Learning Outcomes - Hikmawati, Hikmawati; Sofiya, Rizka; Zakia, Hanna; Islami, Diyan; Rahman, Bq Olivia; Susanti, Susi; Novianti, Tri; Zohriana, Zohriana (AMPLITUDO : Journal of Science and Technology Innovation, 2024)
This study aims to describe the profile of student learning outcomes in the affective, cognitive, and psychomotor domains through the application of the Problem Based Learning (PBL) model supported by three-dimensional media and interactive games in grades V and VI of SD Negeri 29 Ampenan. This type of research is a case study with a descriptive approach. Data collection was carried out using observation sheets to assess the affective domain, a final learning test to assess the cognitive domain, and a performance sheet to assess the psychomotor domain. The learning topics include 4 topics, namely Listening to folk tales., Pancasila in my life, Diseases affecting the musculoskeletal system, and Hearing because of sound. The learning implementation was carried out on July 23, 24, 25, and 26, 2024, respectively. The results showed that the application of PBL with three-dimensional media and interactive games had a positive effect on the three domains of learning outcomes. In the affective domain, students showed increased cooperation, responsibility, and discipline. The cognitive domain recorded a good understanding of the learning concept according to the topic. In the psychomotor domain, students were able to complete practice-based tasks with satisfactory results. These findings support the constructivism theory, which emphasizes the importance of hands-on and interactive experiential learning to enhance deep conceptual understanding. This study recommends the use of innovative media such as three-dimensional and interactive games in the PBL model to enhance students' learning outcomes holistically.